2022
DOI: 10.3389/fimmu.2022.985433
|View full text |Cite
|
Sign up to set email alerts
|

MIS-C: A COVID-19-as sociated condition between hypoimmunity and hyperimmunity

Abstract: Multisystem inflammatory syndrome in children (MIS-C) is a rare, severe complication of COVID-19. A better knowledge of immunological, cellular, and genetic characteristics of MIS-C could help better understand the pathogenesis of the disease and contribute to identifying specific diagnostic biomarkers and develop targeted therapies. We studied 37 MIS-C children at hospital admission and 24 healthy controls analyzing serum cytokines (IFN-α, IFN-β, IFN-γ, IL-6, IL-10, IL-17A, IL-12p70 and TNF), lymphocyte popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
53
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(56 citation statements)
references
References 42 publications
2
53
0
Order By: Relevance
“…An aberrant increase of IL-17 in MIS-C compared to pediatric COVID-19 patients was also detected in the study by Gruber et al in freeze-thawed PBMC samples by ow cytometry 16 . Serum IL-17 was detected higher in MIS-C compared to COVID-19 or healthy controls 11,17 . Th17 cells release IL-17A which stimulates the production of proin ammatory cytokines such as IL-17, IL-22, and IL-26 and play an important role in neutrophils recruitment as well as cardiovascular clinical manifestations 18 .…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…An aberrant increase of IL-17 in MIS-C compared to pediatric COVID-19 patients was also detected in the study by Gruber et al in freeze-thawed PBMC samples by ow cytometry 16 . Serum IL-17 was detected higher in MIS-C compared to COVID-19 or healthy controls 11,17 . Th17 cells release IL-17A which stimulates the production of proin ammatory cytokines such as IL-17, IL-22, and IL-26 and play an important role in neutrophils recruitment as well as cardiovascular clinical manifestations 18 .…”
Section: Discussionmentioning
confidence: 79%
“…Limited studies that investigate cytokine expression in MIS-C involve lymphocyte-speci c cytokine expression after PBMC isolation from fresh, whole peripheral blood, since most published studies predominantly use serum 10,11 or plasma 12,13 in order to evaluate cytokine expression. There is only one study by Rybkina et al based on fresh blood collection and PBMCs isolation that also showed distinct cellular immune responses between MIS-C and uncomplicated COVID-19 patients, however aim of the study was to identify certain transcriptional signature differences of TCR gene expression between MIS-C acute and convalescent phase 14 .…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of MIS-C involves autoinflammatory and/or autoimmune hyperinflammatory processes triggered by SARS-CoV-2. 27,28 In the early stage of infection, the virus triggers macrophage activation followed by stimulation of T helper cells, resulting in cytokine release and B-cell and plasma cell activation. 29 Massive proinflammatory cytokine release stimulates macrophages, neutrophils, and monocytes along with B-cell and plasma cell activation.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, next-generation sequencing (NGS) was performed in samples from 37 MIS-C children at hospital admission and 24 healthy controls from Italy for a panel of 386 genes related to autoimmune diseases, autoinflammation, and primary immunodeficiencies ( Gelzo et al., 2022 ). Similarly, to the present study, the authors identified variants in 34 genes, and 83.3% of patients had at least one variant.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, to the present study, the authors identified variants in 34 genes, and 83.3% of patients had at least one variant. Most genes were related to autoimmune diseases like ATM , NCF1 , MCM4 , FCN3 , and DOCK8 or autoinflammatory diseases associated with the release of IFN-gamma, such as PRF1 , NOD2 , and MEF ( Gelzo et al., 2022 ). Interestingly, three variants identified by the authors were also present in our cohort: PRF1 rs35947132, FCN3 rs532781899, and IFIH1 rs35337543.…”
Section: Discussionmentioning
confidence: 99%